Establishment of Fermentation Kinetic Model of Streptococcus thermophilus JM108 - Wen SUN; Baolei LI; Baochao HOU; Weilian HONG; Jian HE; Chao LIANG; Yu ZHANG; Chaoxin MAN; Yujun JIANG; Ling GUO (Shipin gongye ke-ji)
This study examined the growth and metabolism of Streptococcus thermophilus JM108 to establish a time-varying model that simulated the dynamics of bacterial growth, product synthesis, and substrate consumption. Streptococcus thermophilus JM108 was inoculated into M17 medium. The viable bacteria count, lactic acid content, and glucose content of Streptococcus thermophilus JM108 in the fermentation system were measured every 2 h. The measured values were nonlinearly fitted using the three classical models: Logistic model, Boltzmann model, and SGompertz model. The results of the nonlinear fitting indicated that the Logistic model was the most appropriate for describing the kinetics of bacterial growth, lactic acid generation, and glucose consumption. The R2 values for the three cases were 0.9974, 0.9947, and 0.9964, respectively, all greater than 0.99. The errors between the fitted and experimental values were less than 15%, indicating a good fit. This suggested that the established dynamic model could predict the dynamic changes of the fermentation process. The growth kinetics equation of Streptococcus thermophilus JM108 was \begin{document}$ {\text{y=8.59+}\dfrac{{-2.39}}{\text{1}\text{}\text{+}\text{}{\left(\dfrac{\text{x}}{\text{2.32}}\right)}^{\text{0.02}}} }$\end{document}. The kinetic equation for lactic acid production was \begin{document}${ \text{y=1.05+}\dfrac{{-1.06}}{\text{1+}{\left(\dfrac{\text{x}}{\text{3.67}}\right)}^{\text{3.23}}}} $\end{document}. The kinetic equation for glucose consumption was \begin{document}${ \text{y=0.02+}\dfrac{\text{0.15}}{\text{1+}{\left(\dfrac{\text{x}}{\text{3.47}}\right)}^{\text{3.90}}}} $\end{document}. A fermentation kinetics model was established for Streptococcus thermophilus JM108 to provide theoretical support for describing the fermentation process.